1964
DOI: 10.1093/bja/36.7.438
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Problems of Intestinal Obstruction in Adults

Abstract: The problems of anaesthetizing ill patients with intestinal obstruction arise from the possibility of aspirating stomach contents, and from attempts to produce adequate abdominal muscular relaxation. The hazards and mechanisms of both vomiting and regurgitation are discussed in detail. On this basis, the rationale of preventing aspiration is described. For the production of adequate abdominal relaxation, the muscle relaxants appear to be the method of choice, despite occasional abnormal responses in these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…11,12,29,30 However, previous studies that have evaluated aspiration during bag-mask ventilation have been limited to the examination of anesthetized healthy volunteers, have used epigastric auscultation to detect gastric insufflation as a surrogate for aspiration, and have reported conflicting results. 14,3136 Given the low incidence of operator-reported aspiration during tracheal intubation of critically ill adults, 7,37,38 determining whether bag-mask ventilation increases the relative risk of aspiration by 50% would require a trial enrolling approximately 4000 patients. However, our trial provides some reassurance, since the incidence of operator-reported aspiration was numerically lower in the bag-mask ventilation group than in the no-ventilation group.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,29,30 However, previous studies that have evaluated aspiration during bag-mask ventilation have been limited to the examination of anesthetized healthy volunteers, have used epigastric auscultation to detect gastric insufflation as a surrogate for aspiration, and have reported conflicting results. 14,3136 Given the low incidence of operator-reported aspiration during tracheal intubation of critically ill adults, 7,37,38 determining whether bag-mask ventilation increases the relative risk of aspiration by 50% would require a trial enrolling approximately 4000 patients. However, our trial provides some reassurance, since the incidence of operator-reported aspiration was numerically lower in the bag-mask ventilation group than in the no-ventilation group.…”
Section: Discussionmentioning
confidence: 99%
“…Normally this hazard is prevented by preoxygenation, rapid intravenous induction with a barbiturate and intubation during cricoid pressure. 2 In the circumstances we judged that rapid induction with a barbiturate in the semirecumbent position would have resulted in postural hypotension. 3 Whilst this could have been avoided by the use of intravenous ketamine, two other problems would have remained.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Wylie 6 proposed the concept of 'not inflating' the patient's lungs with oxygen until tracheal intubation had been accomplished in 1963. This view was subsequently reinforced by Stevens 7 in 1964. Both these authors hypothesised that positive pressure ventilation before intubation increases the risk of gastric inflation and the potential for regurgitation.…”
mentioning
confidence: 88%
“…Both these authors hypothesised that positive pressure ventilation before intubation increases the risk of gastric inflation and the potential for regurgitation. 6,7 Incorporation of these changes into practice led to the origin of the concept of 'modified' RSI. Thus, we believe that the authors performed 'traditional' RSI and not the 'modified' RSI technique.…”
mentioning
confidence: 99%